Capabilities and prospects of the East Asia Very Long Baseline Interferometry Network. (February 2018) - An, T.; Sohn, B.; Imai, H.
Abstract The very long baseline interferometry (VLBI) technique offers angular resolutions superior to any other instruments at other wavelengths, enabling unique science applications of high-resolution imaging of radio sources and high-precision astrometry. The East Asia VLBI Network (EAVN) is a collaborative effort in the East Asian region. The EAVN currently consists of 21 telescopes with diverse equipment configurations and frequency setups, allowing flexible subarrays for specific science projects. The EAVN provides the highest resolution of 0.5 mas at 22 GHz, allowing the fine imaging of jets in active galactic nuclei, high-accuracy astrometry of masers and pulsars, and precise spacecraft positioning. The soon-to-be-operational Five-hundred-meter Aperture Spherical radio Telescope (FAST) will open a new era for the EAVN. This state-of-the-art VLBI array also provides easy access to and crucial training for the burgeoning Asian astronomical community. This Perspective summarizes the status, capabilities and prospects of the EAVN. The East Asia Very Long Baseline Interferometry Network (EAVN) consists of 21 radio telescopes whose equipment and frequency setup allow fine imaging of jets in active galaxies, high-accuracy astrometry of masers and pulsars, and spacecraft positioning.